Recent Advances in Thin Film Electronic Devices - Dong, Chengyuan (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This reprint is a collection of the papers from the Special Issue "Recent Advances in Thin Film Electronic Devices" in Micromachines. In this reprrint, 1 editorial and 11 original papers about recent advances in the research and development of thin film electronic devices are included. Specifically, three research fields are covered: device fundamentals (5 papers), fabrication processes (5 papers), and testing methods (1 paper). The experimental data, simulation results, and theoretical analysis presented in this reprint should benefit those researchers in flat panel displays, flat panel sensors, energy devices, memories, and so on.